The impact of stock, energy and foreign exchange markets on the sugar market - Nikolaos Sariannidis (International Journal of Economic Sciences and Applied Research, 2010)
This study examines the effect of financial factors on the sugar market by using Generalized Autoregressive Conditional Heteroskedasticity (GARCH) models. The results show that changes in capital and energy markets returns have a positive impact on the mean returns of Sugar futures as opposed to changes in volatility returns of the exchange rate of the U.S. Dollar/ Yen that affect it negatively. Finally, the structural analysis of volatility with the GARCH model has shown that current volatility is more influenced by past volatility rather than by the previous day shocks.
Keywords: G15; Q13; Q14; 330; GARCH model; sugar futures; crude oil; ethanol; exchange rates